Metode Dakwah Penyuluh Agama Islam Dalam Meningkatkan Kesadaran Beragama Masyarakat Di Gang Madirsan Desa Bangun Sari Kecamatan Tanjung Morawa - Ihsan Azhari (Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study aims to describe the implementation of Qur’anic Healing as a stress-coping strategy among Qur’an memorization students at Pondok Pesantren Tahfidz Qur’an Al-Kautsar Curup. Using a qualitative descriptive method, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that students’ stress arises from internal factors—such as mental readiness, motivation, and physical condition—and external factors, including environmental pressure and memorization targets. The application of Qur’anic Healing involves dzikr and tadabbur of the Qur’an, murottal therapy, and prayer-based spiritual conviction. These practices effectively calm emotions, enhance focus, and strengthen psychological resilience. Furthermore, Qur’anic value-based social support reinforces students’ ability to cope with academic and emotional pressures. Overall, Qur’anic Healing serves as an integrative spiritual approach that not only helps manage stress but also improves memorization quality and deepens students’ religious and emotional well-being